Seven Thousand Years of Native American History in the Sacramento Valley : Results of Archaeological Investigations near Hamilton City, California - Hildebrandt, William R.; McGuire, Kelly R. (Book collections on Project MUSE., 2022)
"This project was the result of cultural resource management (CRM) investigations along the Sacramento River and floodplain for new levee construction and to degrade the existing levee. The archaeological record uncovered by these investigations provides new insights into the origin of intensive acorn use in California, the evolution of fishing technologies along the Sacramento River and its adjacent backwater habitats, the origin of bow-and-arrow technology, the rise of sedentism and logistical hunting organization, the interregional exchange of obsidian and shell beads, and periods of violence among the local people, some resulting in brutal outcomes"--